A new species of Geranium L. (Geraniaceae) from Kashmir Himalaya, India - Hurrah, Imtiyaz Ahmad; Shukla, Aparna R.; Wagh, Vijay V. (Phytotaxa, 2023)
Amongst the materials of Geranium pratense L., presence of some unusual specimens was revealed during the consultation of the Kashmir University Herbarium (KASH). Following field work and macro-micro morphological studies of collected specimens, a new species Geranium dachigamensis is recognised from Dachigam National Park and is described and illustrated here. The comparison of the new taxon with its allied species, along with notes on conservation status, habitat & distribution are provided.